T Cell Activating Thermostable Self‐Assembly Nanoscaffold Tailored for Cellular Immunity Antigen Delivery - Jinsong Zhang; Jianghua Yang; Qianlin Li; Ruihao Peng; Shoudong Fan; Huaimin Yi; Yuying Lu; Yuanli Peng; Haozhen Yan; Lidan Sun; Jiahai Lu; Zeliang Chen (Advanced Science, 2023)
Abstract Antigen delivery based on non‐virus‐like particle self‐associating protein nanoscffolds, such as Aquifex aeolicus lumazine synthase (AaLS), is limited due to the immunotoxicity and/or premature clearance of antigen‐scaffold complex resulted from triggering unregulated innate immune responses. Here, using rational immunoinformatics prediction and computational modeling, we screen the T epitope peptides from thermophilic nanoproteins with the same spatial structure as hyperthermophilic icosahedral AaLS, and reassemble them into a novel thermostable self‐assembling nanoscaffold RPT that can specifically activate T cell‐mediated immunity. Tumor model antigen ovalbumin T epitopes and the severe acute respiratory syndrome coronavirus 2 receptor‐binding domain are loaded onto the scaffold surface through the SpyCather/SpyTag system to construct nanovaccines. Compared to AaLS, RPT‐constructed nanovaccines elicit more potent cytotoxic T cell and CD4+ T helper 1 (Th1)‐biased immune responses, and generate less anti‐scaffold antibody. Moreover, RPT significantly upregulate the expression of transcription factors and cytokines related to the differentiation of type‐1 conventional dendritic cells, promoting the cross‐presentation of antigens to CD8+ T cells and Th1 polarization of CD4+ T cells. RPT confers antigens with increased stability against heating, freeze‐thawing, and lyophilization with almost no antigenicity loss. This novel nanoscaffold offers a simple, safe, and robust strategy for boosting T‐cell immunity‐dependent vaccine development.